Effect of Osmotic Shocks on Sodium Regulation and Na-K-ATPase Activity of Pacific White Shrimp (Litopenaeus vannamei Boone, 1931): Sodium Regulation and Na-K-ATPase Activity of Pacific White Shrimp - Anggoro, Sutrisno; Purwanti, Frida; Taufani, Wiwiet Teguh; Nakamura, Kaworu (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2018)
Effects of Millieu exterieur osmotic shocks on sodium (Na+)regulation and Na-K-ATPase activity of Litopenaeus vannamei (Boone, 1931) were investigated. Active uptake of sodium and Na-K-ATPase enzyme activity followed similar pattern; they decreased to minimum levels and became almost constant after the shrimp was reared in an isosmotic medium (875.40 mOsm L–1 H2O ∞ 30 g L–1). The research was conducted by experimental laboratory method using completely randomized design with four treatments and three replicates. This study showed that Na-K-ATPase activity was directly affected the active uptake of sodium. Cultivated shrimps which were reared in an isosmotic medium regulated their haemolymph osmotic concentration passively; thus, decreased their osmotic works and increased their potential energy needed for moulting process and growth. Active transport of Na+ and the activity of Na-K-ATPase in the body fluids of L. vannamei shrimp followed similar pattern, at which they decreased to minimum levels and became almost constant after the shrimps were reared in and isosmotic medium (± 30 g L–1 ∞ 875.40 mOsm L–1 H2O).